Determinants of Emotional Beliefs about Shared Values in Organizations - Galih Panjalu Pramono; Dyah Purwaningrum; Sutaat Sutaat (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the impact of competency development on affective commitment mediated by career development. The population in this study were all teachers at a junior high school in Banyumanik, Semarang, totaling 52 people, with a sample of all members of the population. The analysis tool uses regression and sobel analysis. The results of the study found that competency development has a positive effect on career development, career development has a positive effect on affective commitment. competency development has a positive effect on affective commitment. career development is able to mediate the effect of competency development on affective commitment